PENDAMPINGAN INTERNALISASI DAN IMPLEMENTASI MAKNA PERINGATAN MAULID NABI MUHAMMAD SAW BAGI PESERTA DIDIK DI SMKN 2 PARIAMAN - Leni Purnama Sari; Hamzah Irfanda; Aulia Zahara; Farida Ariani (Universitas Sumatera Barat, 2025)
The mentoring program on the internalization and implementation of the meaning of the Prophet Muhammad’s birthday (Maulid Nabi) commemoration for students at SMKN 2 Pariaman aims to instill the values of the Prophet’s exemplary character as a foundation for developing religious, social, and moral attitudes. The method employed was a participatory approach through lectures, discussions, and practical activities that actively involved students. The results indicate that students were able to understand the essence of Maulid Nabi not merely as a ceremonial tradition, but as a moment of spiritual reflection and the actualization of noble moral values in daily life. The positive impact of this mentoring was evident in the students’ increased awareness of the importance of emulating the Prophet’s character in honesty, discipline, responsibility, and social care. Therefore, this activity provides a significant contribution to strengthening Islamic character formation among the younger generation in the school environment.